NEW METHOD OF PARTIAL NEPHRECTOMY WITH SELECTIVE PARENCHYMA CLAMPING - S. Kh. Al’-Shukri; M. S. Mosoyan; D. Yu. Semyonov; A. M. Esayan; D. M. Il’In (Вестник хирургии имени И.И. Грекова)
The authors suggested a new method of performance of open, laparoscopic and robot-assisted partial nephrectomy using specially developed instruments for selective parenchyma clamping in order to improve the functional results of renal cell carcinoma treatment. The operation with clamping of renal vessels was carried out in 86 cases and clamping of renal parenchyma was used in 24 cases. It was shown, that the open, laparoscopic and robot-assisted partial nephrectomy could be safely performed in conditions of selective ischemia of the renal parenchyma without clamping of renal vessels.